Faktor – Faktor yang Mempengaruhi Identitas Diri - Candra Ari Ramdhanu (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2019)
Self identity is an important component that shows the individual's personal identity. Individuals who succeed in forming their identities will help them to take the right role in their lives, while for teenagers who do not succeed in forming their identities, they will be confused about their role in life. Many factors influence self-identity. Gender, birth order, parental marital status, and parenting affect adolescent self-identity. This article will describe the correlation between these factors and self-identity.